Student Responses and Learning Outcomes in STEM Learning Based on Project Based Learning (PjBL) - Rina Dwi Maryanti; Shirly Rizki Kusumaningrum; Mardhatillah Mardhatillah (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2025)
This study investigates students’ responses and learning outcomes in STEM education through a Project Based Learning (PjBL) approach focused on natural disaster simulations in fifth-grade elementary students. Although a digital STEM based disaster learning model has been shown to significantly improve elementary students’ disaster adaption abilities through quasi experimental research, existing studies generally emphasize digital simulations rather than real context thematic project experiences in primary schools. Therefore, the novelty of this research lies in the integration of STEM and PjBL within thematic learning for disaster context education, addressing a gap in studies at the elementary level, particulary in Indonesia. This descriptive quantitative study involved 15 students and employed learning outcome assessments and student response questionnaires. Results revealed that all students achieved mastery learning with an average score of 94.73. Student responses were highly positive, with an average questionnaire score of 3.80 out of 4, indicating strong engagement and improved conceptual understanding during the disaster simulation project. The integrated STEM-based PjBL approach fostered active student involvement, collaboration, and critical thinking skills. These findings demonstrate the effectiveness of this model in enhancing elementary science learning quality and provide a promising approach for thematic, student centered instruction in disaster education contexts.